Acute pulmonary embolism in COVID-19 patient: a case report of free-floating right heart thrombus successfully treated with fibrinolysis. Issue 1 (28th December 2020) - Scudiero, Fernando; Pitì, Antonino; Keim, Roberto; Parodi, Guido
Abstract: Background: Despite the fast-growing understanding of the coronavirus disease 2019 (COVID-19), patient management remains largely empirical or based on retrospective studies. In this complex scenario, an important clinical issue appears to be represented by the high prevalence of thromboembolic events, but the data regarding high-risk pulmonary embolism (PE) is still not available. Case summary: A patient with COVID-19 developed sudden shortness of breath and hypoxia. Early echocardiographic diagnosis of high-risk PE related to right heart thrombus was performed. Systemic thrombolysis was administered with excellent clinical and haemodynamic response. Discussion: Pulmonary thromboembolism is a common occurrence in severe COVID-19 infection. In our experience, systemic thrombolysis proved to be effective and for this reason may be considered for life-threatening PE in COVID-19 patients.